Impact of preoperative antithrombotic discontinuation duration on clinical outcomes following hard channel surgery for chronic subdural hematoma - Cao, Wen-Yu; Li, Jin-ping (Frontiers in Neurology, 2025)
BackgroundChronic subdural hematoma (CSDH) is a prevalent neurosurgical disorder with an increasing global incidence, particularly among the elderly. In recent years, minimally invasive burr-hole drainage, employing a small-diameter puncture needle in conjunction with a closed drainage system, has emerged as a preferred first-line intervention. This technique is associated with several clinical advantages, including lower recurrence rates, fewer postoperative complications, reduced mortality, and shorter operative durations and hospital stays. Despite these benefits, recurrence rates still range from 5 to 30%. One unresolved issue is the impact of preoperative antithrombotic therapy on recurrence and perioperative complications, which remains controversial and poorly defined in the current literature.ObjectiveThis study aimed to optimize preoperative antithrombotic management in patients with CSDH through a retrospective analysis.MethodA retrospective review was conducted on patients diagnosed with CSDH who underwent hard-channel puncture and drainage at Beijing Chaoyang Hospital, Capital Medical University, between December 2016 and March 2023. Patients were stratified into three groups according to their preoperative antithrombotic drug use and discontinuation status: (1) no antithrombotic use; (2) adequate discontinuation (≥7 days prior to surgery); and (3) inadequate discontinuation (<7 days). The relationship between the duration of antithrombotic discontinuation and postoperative outcomes was analyzed to inform evidence-based perioperative management strategies.ResultThe results showed no significant association between preoperative antithrombotic discontinuation and major clinical outcomes. However, insufficient discontinuation was associated with a significant prolongation of hospital stay.ConclusionInsufficient preoperative antithrombotic discontinuation did not significantly affect major clinical outcomes in patients with CSDH undergoing hard-channel puncture drainage. However, it was associated with prolonged hospital stay. These findings support individualized preoperative antithrombotic management to optimize safety and efficacy while minimizing hospitalization duration.